Property Tax as a Source of Income for Communes, as an Example for Communes: Zapolice, Zduńska Wola, Margonin - Kozłowska, Marta (Journal of Finance and Financial Law, 2015)
The article includes theoretical representation of the specifics of own revenues communes and the empirical part devoted to assessing the significance of property tax revenues of municipalities in two facets. The research method is the analysis of financial statements that I have made on the basis of documents drafted by the communes: Zapolice, Zduńska Wola, Margonin for the interval 2008–2012.